Improving economic assessment and decision-making for managed retreat through CBA+: a targeted literature review - Cross, Benjamin; Doberstein, Brent; Lueck, Vanessa (Frontiers in Climate, 2025)
There is growing recognition that managed retreat, also known as strategic relocation, could be an increasingly important adaptation measure in the face of climate change and rising natural hazard risk. However, managed retreat’s potential benefits are limited by challenges in funding, negative participant experiences, public and political opposition, uncertainty in long-term climate change and natural hazard risk, and equity concerns, all of which increase the complexity of managed retreat decision-making. While there is some research on how economic assessment tools can be used to aid in managed retreat decision-making, there is a knowledge gap in how these practises contribute to both the causes and potential resolution of the challenges associated with managed retreat. To begin to fill this gap, this paper presents a targeted literature review on the nexus between managed retreat, cost–benefit analysis of climate change adaptation and natural hazard risk reduction, and alternative economic assessment and decision-making tools. We identify connections between economic assessment practises and the primary challenges associated with managed retreat and then present several avenues where changes or additions to standard economic assessment approaches such as cost–benefit analysis (which we collectively refer to as ‘CBA+’) could lead to better managed retreat outcomes. Finally, we present a framework and 10 key principles that summarise key aspects of CBA+ to help agencies involved in managed retreat improve outcomes through economic assessment and decision-making process design. The most important key principles are the context- and community-specific design of economic assessment and decision-making processes, and the need for ongoing and thorough community engagement and co-production.